Geología de los cuadrángulos de Puerto Luz, Colorado, Laberinto, Puerto Maldonado, Quincemil, Masuco, Astillero y Reserva Tambopata. Hojas: 26-u, 26-v, 26-x, 26-y, 27-u, 27-v, 27-x, 27-y – [Boletin A 81] - Palacios Moncayo, Oscar (1996)
189 p.